ANALISIS PENGARUH CITA RASA, KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN - Arbiantoro, Tri; Maduwinarti, Ayun; Pujianto, Agung (Jurnal Dinamika Administrasi Bisnis, 2018)
The low sales rate of Gibrass Meatballs compared to ordinary meatballs depot is the background of this research. The title of this research is "Analysis of Taste Influence, Quality of Service, and Price Against Customer Satisfaction (case study of Gibrass Meatballs Jl Kutisari Selatan II No. 45 Surabaya)". This research uses quantitative descriptive method. The population is the customer whoever bought Bakso Gibrass Surabaya, the samples taken as many as 96 respondents with sampling technique purposive sampling.Data collection through questionnaire likert scale 1-5, data analysis technique using instrument test, classical assumption and hypothesis test. The results obtained conclusion as follows: 1. partially the sense of influence and significant, the quality of service has no significant effect and the price effect with the negative direction and significant. 2. Simultaneously taste, quality of service and price have a positive and significant impact on customer satisfaction.Â Keywords:taste, quality of service, price, customer satisfaction